Molecular Analysis of Mycobacterium tuberculosis Isolated in the North Central Zone of Nigeria - Benjamin David Thumamo Pokam; Dorothy Yeboah-Manu; Lovett Lawson; Prisca Wabo Guemdjom; Ruth Okonu; Laura Madukaji; Nchawa Yangkam Yhiler; Anne Ebri Asuquo (Springer, 2019)
Tuberculosis (TB) incidence in Nigeria is high, with a significant burden of TB/Human Immunodeficiency Virus (HIV). Genotyping and drug susceptibility of Mycobacterium tuberculosis Complex (MTBC) are important in order to improve the control of the disease. This study sought to determine drug susceptibility and genetic diversity of MTBC in the country. The sputum samples of 202 patients [133 (65.8%) males/69 (34.2%) females] were collected in the North Central zone of Nigeria and cultured using Lowenstein-Jensen medium. Immunochromatography for the primary identification and Drug Susceptibility Testing (DST) by proportion method, as well as IS6110 typing, regions of difference 1, 4, 9, 12, 702, and 711, and spoligotyping were carried out on the isolates. Following the DST on 202 isolates, 51 (25.2%) showed resistance to at least one drug. Multidrug resistance was observed in 29/202 (14.4%) cases. HIV positivity [37/202 (18.3%) patients] was associated with rifampicin 9/37 (24.3%) resistance (p = 0.012) as well as gender (p = 0.009). Of the 202 isolates, 150 (74.3%) were identified as the Cameroon sublineage, followed by the UgandaI, Haarlem, and West Africa 1 with 18 (8.9%), 10 (5%), and 6 (3%), respectively. The LAM10_CAM was the most prevalent genetic family [128/202 (63.4%)], with the shared international type 61 [111 (55%) isolates] the largest cluster. Gender (p = 0.038) and age (p = 0.015) had significant associations with the LAM10_CAM family but neither with HIV (p = 0.479) nor drug resistance. Rifampicin resistance in TB/HIV coinfected patient is a major concern in the study area. The Mycobacterium africanum lineage showed a marked decrease, and the need to educate females most at risk of TB/HIV coinfection is advocated.